EVALUATION OF TRANSFORMED LAYER HARDNESS OF DLC COATING AFTER FRICTION TEST (Jurnal Teknologi (Sciences & Engineering), 2016)
Diamond-like carbon (DLC) provide very excellence performance in term of friction coefficient and wear resistance under boundary   lubrication. the  nano characteristic of the transformed  layer has not  been studied  in terms  of its  hardness  which is believed to  have a significant  effect in the tribological  performance. This study presented the scratch test of the DLC transformed layer was obtained from the AFM scratch test that governs the friction behavior of DLC. As a result, the hardness of the DLC transformed layer depends on the oil temperature, where the sliding interface of DLC softened during the friction test due to graphitization process